Pola Regulasi Pemerintah Daerah dalam Memitigasi Tumpahan Minyak di Wilayah Pesisir Pantai Kabupaten Bangka Tengah Berdasarkan Prinsip Sustainable Development Goals - Ardalina, Dwi Okta; Amelia, Risna; Nopiani, Nela (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Oil or oil spill is one of the many Marine pollutants that can stem from errors in tanker activity or from the Mediterranean to drift downstream. An example of the case is the incidence of an oil spill in the region of the central bangka area that happened on the coast 12 miles away, where oil spills have contaminated the outlying areas and other seas like kobatin, and deep-sea arung coast. The purpose of the writer's article is to find out how the government's regulatory pattern of dealing with the impact that oil spill on the seas and beaches in the central bangka county has on oil, and the writer would also like to see a perspective on how oil spills are completed, in order to ensure that local life is as smooth as it was before the oil spill.